Accounting System Development Methodology - Irawati, Chintia; Hazmi, Yusri; Zulfiana, Dina; Rismadara, Nur (West Science Interdisciplinary Studies, 2024)
An accounting system development methodology is a series of procedures implemented by systems analysts to improve a company's current accounting system. Library Research (Library Research) is a method or approach used by researchers. Library research and inquiry have more than just the functions mentioned in the context of obtaining research data. This means that library research is only limited to library collection materials and does not require field research. However, library research is a method of obtaining data that involves reviewing books, literature, notes and various reports that are relevant to the problem at hand, in accordance with the opinions of experts. In the process of implementing an inadequate Accounting Information System (AIS) in a company, there are several irregularities that occur. Because of this, the company's Accounting Information System needs to be developed in a better direction. This is to ensure that the information the company needs is more appropriate.